2020
DOI: 10.1002/jmv.26377
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of hepatitis E in Yavatmal, India, 2019

Abstract: Hepatitis E, a public health concern in developing countries, frequently presents in epidemic, as well as in sporadic forms. This study investigated an outbreak of viral hepatitis at Yavatmal, Maharashtra, India in March 2019. Blood samples from 10 patients were received at Indian Council of Medical Research‐National Institute of Virology, Pune to test for the presence of enterically transmitted hepatitis viruses. Subsequently, 49 suspected cases were screened for anti‐hepatitis E virus (HEV)/hepatitis A virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Another outbreak in India was explained by the close vicinity of the drinking water pipelines and a drainpipe. The drain water contaminated the domestic water supply [ 36 ]. Changing faulty water pipes and segregating them from drainpipes reduced the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Another outbreak in India was explained by the close vicinity of the drinking water pipelines and a drainpipe. The drain water contaminated the domestic water supply [ 36 ]. Changing faulty water pipes and segregating them from drainpipes reduced the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…In the last couple of decades, HEV has been reported to be endemic in many developing and developed countries [14,16,18,19,22,23,28,29]. However, the seroprevalence of hepatitis E showed considerable interregional and intraregional variation ranging from 1% in Iran to 49.8% in Bangladesh [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes 1 to 4 are reported to cause human infection [11]. Genotypes 1 and 2 are endemic to Southeast Asia, Africa, and South America and typically spread via contaminated water [14][15][16][17]. Genotypes 3 and 4 are found in industrialized countries including the United States, Europe, and Japan and are transmitted through ingestion of contaminated meat, usually pork, or blood transfusions [4,14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…198 In India and Bangladesh or China, HEV-1 or HEV-1 and HEV-4 are the main HEV genotypes, respectively. [199][200][201][202][203] A recent metaanalysis demonstrated that among nonpregnant participants, the pooled proportion of HEV in the etiology of virus-related ALF was estimated to be 40.0%, 30.0%, and 61.0% in India, China, and Bangladesh, respectively. 204 In pregnant Indian women, the combined proportion of HEV in the etiology of viral-related ALF was 71.0%.…”
Section: Mizuo Et Al Compared Various Features Between Patients Infectedmentioning
confidence: 99%